2021
DOI: 10.1111/ppa.13504
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic progress of beet necrotic yellow vein virus: Evidence from an investigation in Japan spanning half a century

Abstract: Beet necrotic yellow vein virus (BNYVV) is the causal agent of rhizomania, the most serious sugar beet disease worldwide. Since the first finding in Japan in 1969, BNYVV became widespread throughout Hokkaido in a few decades and led to the introduction of Rz1‐resistant sugar beet cultivars in the 1990s. Here, we report the historical progress of the BNYVV epidemic in Hokkaido from 1969 to 2019. Previous analysis on samples from 1991 showed that BNYVV isolates were classified into three strains (named O, D, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The P-type currently has only a minor distribution despite its clear fitness advantage in Rz1 -resistant varieties that are grown in all European sugar beet-growing areas. However, a recent analysis of many BNYVV populations from Japan revealed that the incidence of Asian A-type isolates possessing an RNA5 (J-type) had increased in the past few decades (1991–2019) probably with the introduction of resistant varieties [49]. Such current population studies are missing in Europe, but our results strengthen their importance.…”
Section: Discussionsupporting
confidence: 61%
“…The P-type currently has only a minor distribution despite its clear fitness advantage in Rz1 -resistant varieties that are grown in all European sugar beet-growing areas. However, a recent analysis of many BNYVV populations from Japan revealed that the incidence of Asian A-type isolates possessing an RNA5 (J-type) had increased in the past few decades (1991–2019) probably with the introduction of resistant varieties [49]. Such current population studies are missing in Europe, but our results strengthen their importance.…”
Section: Discussionsupporting
confidence: 61%
“…Finally, the presence of J and P type RNA5 in populations from Germany and other European countries was surprising for us, but it highlights the need for such monitoring studies. Interestingly, a recent study observed that the incidence of J type RNA5 has increased over time in Japan (1969–2019), most probably due to the introduction of Rz1 ‐resistant cultivars (Nakagami et al, 2021). It remains to be shown whether such a shift in the genome composition will also occur in European BNYVV populations.…”
Section: Discussionmentioning
confidence: 99%
“…Natural populations of the P type are resistance-breaking (Pferdmenges et al, 2009;Bornemann and Varrelmann, 2011;Bornemann et al, 2015) and we recently showed by reverse genetics that this is due to the presence of RNA5 (Müllender et al, 2022). A similar resistance-breaking property has been suggested for the J type RNA5 in Asian A-and B type isolates, but experimental evidence by reverse genetics is lacking (Nakagami et al, 2021;Tamada et al, 2021). Interestingly, we found recently in resistance-breaking isolates from European countries both RNA5 species (J-and P type) in association with A-and B type (Liebe and Varrelmann, 2022).…”
Section: Introductionmentioning
confidence: 66%
“…The P type RNA5 belongs originally to P type isolates and is the major driver of Rz1 resistance-breaking by this virus type (Müllender et al, 2022). In contrast, evidence for the resistance-breaking effect of the RNA5 belonging to the J type group is based on experiments using natural virus populations (Nakagami et al, 2021;Tamada et al, 2021). Both RNA5 species display some sequence variation in the encoded P26 protein, and therefore, we wanted to compare the resistancebreaking properties of both in the background of our BNYVV A type clone.…”
Section: Discussionmentioning
confidence: 99%